2021
DOI: 10.1523/eneuro.0403-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine-Induced Alteration of Working Memory Utility during Oculomotor Foraging Task in Monkeys

Abstract: The authors thank M. Suzuki for administrative help; H. Miyaguchi for animal care and training; N. Tsuchida for comments on statistical analysis; M. Takei and M. Kusuzaki for manufacturing some equipment; N. Kamibayashi for providing illustrations; and other lab members for discussions. Animals were provided by the National Bio-Resource Project. RS was supported by the Research Fellowship for Young Scientists (DC1) from the Japan Society for the Promotion of Science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 89 publications
1
7
0
Order By: Relevance
“…It indicates that ketamine impairs the retrieval of well-learned abstract rules in the AVM task, which is in line with a previous study showing that anesthetic ketamine impaired the retrieval of information from post-training memory components (Boultadakis & Pitsikas, 2011). The ketamine-induced impairments in WM have been reported in many previous studies in rodents (Moosavi et al, 2012, Mathews et al, 2018, Pitsikas & Carli, 2020, monkeys (Sawagashira & Tanaka, 2021, Roussy et al, 2021, Condy et al, 2005, Skoblenick & Everling, 2012, Blackman et al, 2013 and humans (Ahn et al, 2003, Honey et al, 2004, Koychev et al, 2017. In this study, we found that the low doses of ketamine consistently reduced the correct percentage over 1 h in both AVM and AVM+WM tasks.…”
Section: Discussionsupporting
confidence: 91%
“…It indicates that ketamine impairs the retrieval of well-learned abstract rules in the AVM task, which is in line with a previous study showing that anesthetic ketamine impaired the retrieval of information from post-training memory components (Boultadakis & Pitsikas, 2011). The ketamine-induced impairments in WM have been reported in many previous studies in rodents (Moosavi et al, 2012, Mathews et al, 2018, Pitsikas & Carli, 2020, monkeys (Sawagashira & Tanaka, 2021, Roussy et al, 2021, Condy et al, 2005, Skoblenick & Everling, 2012, Blackman et al, 2013 and humans (Ahn et al, 2003, Honey et al, 2004, Koychev et al, 2017. In this study, we found that the low doses of ketamine consistently reduced the correct percentage over 1 h in both AVM and AVM+WM tasks.…”
Section: Discussionsupporting
confidence: 91%
“…We injected a subanesthetic dose of ketamine 0.5 mg/kg (Daiichi-Sankyo Co., Tokyo, Japan) intramuscularly for transient and reversible manipulation of schizophrenia symptoms. The dosage of ketamine was determined based on previous pharmacological studies in monkeys ( Pouget et al, 2010 ; Sawagashira and Tanaka, 2021 ) and marmosets ( Selvanayagam et al, 2021 ), so that marmosets could perform the free-viewing task. To avoid the development of the drug tolerance and cumulative effect, injections of ketamine were performed once a week.…”
Section: Methodsmentioning
confidence: 99%
“…Early human studies showed that high doses of ketamine strongly affected characteristics of eye movements ( Radant et al, 1998 ), and it was subsequently shown that even low doses reproduce some of the abnormalities seen in subjects with schizophrenia, such as reduced eye acceleration during initiation, reduced closed loop gain ( Weiler et al, 2000 ). Injections of subanesthetic dose of ketamine 0.3–0.5 mg/kg in non-human primates reproduce various sensory and cognitive dysfunctions of schizophrenia, such as dysfunction of the visual working memory ( Sawagashira and Tanaka, 2021 ) and impaired visual contextual integration ( Schielke and Krekelberg, 2021 ) in macaques, deficits in executive function in marmosets ( Kotani et al, 2016 ). Recently, it has been reported in marmosets that ketamine also induced disruption of scan paths, with limited effects on saccade motor control during free-viewing of face images ( Selvanayagam et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this previous study MIA increased the variability of the starting phase of precession; however, in both cases the consequence would be a decrease in the accuracy of sequential ordering during the theta sequences that may underlie aspects of sequential memory. While impairments in temporal processing and sequential ordering are well documented in individuals with schizophrenia, their first-degree relatives, and other at-risk individuals ( Ciullo et al, 2016 , 2018 ; Liu et al, 2020 ; Nour et al, 2021 ; Thoenes and Oberfeld, 2017 ), the effects of ketamine on such processes are less well investigated ( Brulé et al, 2021 ; Coull et al, 2011 ; Sawagashira and Tanaka, 2021 ). Ketamine is, however, known to induce several symptoms of schizophrenia in humans that could potentially involve a sequential component ( Malhotra et al, 1996 ; Morgan et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%